Pelatihan Pembuatan Urea Molasses Block (UMB) pada Kelompok Ternak ''Satria Kelud Perkasa" Desa Gadungan Kecamatan Wates Kabupaten Kediri - Anifiatiningrum; Andaruisworo, Sapta; Yuniati, Erna; Solikin, Nur; Tanjungsari, Ardina; Fauzi, Moh. Mimbar; Rohman, Alfan Nur; Ariana, Melati; Reymonita, Ocha Meylda (Jurnal Pengabdian Masyarakat Nusantara, 2025)
The availability of quality feed for ruminant livestock remains a major challenge for smallholder farmers, especially during the dry season when forage resources become limited. One practical solution is the utilization of Urea Molasses Block (UMB) as a low-cost supplementary feed that is easy to produce and capable of improving feed intake and digestibility. This community service program aimed to enhance the knowledge and technical skills of members of the “Satria Kelud Perkasa” Livestock Group in Gadungan Village, Wates District, Kediri Regency through training on the production of UMB using locally available ingredients. The training was conducted using lectures, demonstrations, and hands-on practice. Program effectiveness was evaluated through pre-test and post-test assessments to measure participants’ knowledge improvement. The results showed a significant increase in participants’ understanding of the functions, composition, and production techniques of UMB. Participants successfully completed all stages of production—including weighing ingredients, mixing, molding, and drying—and produced UMB blocks with good physical quality that were readily accepted by livestock. The activity also strengthened the group’s independence in providing supplementary feed, thereby improving feed efficiency and the potential productivity of their ruminants. This program demonstrates that a participatory approach combined with simple technology transfer is highly effective in improving farmers’ skills and encouraging the adoption of innovations. It is expected that the livestock group will continue producing UMB independently and apply it sustainably in their ruminant feed management.